Enhancing Efficiency Via Digital Marketing and Financial Management of MSME Sari Buah Idaman - Abdillah, Fatimah; Tullah, Dewi Sarifah; Sudradjat; Asyifa , Siti; Febriyan; Callista, Christine; Febrian, Jan; Lauwsetia, Chessa Auriel (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2025)
The main product of Sari Buah Idaman (SBI), a micro, small, and medium-sized enterprise (MSME) in the food and beverage sector, is nutmeg juice. Currently, only nutmeg seeds have a high economic value, so attention needs to be paid to the utilization of nutmeg flesh in nutmeg juice products. This study aims to describe the impact of training and mentoring from digital marketing and finance on enhancing the knowledge of Sari Buah Idaman members. This quantitative research will use a paired sample t-test, sampling both before and after the training, to explain the influence of training and mentoring. All the participants who became respondents in this study were employees of Sari Buah Idaman. The study's results demonstrate the significant impact of training and assistance in enhancing the understanding of digital technology utilization in the marketing and financial management of Sari Buah Idaman. Through the development of knowledge, MSMEs will continue to grow and succeed.